The Analysis Study of Prevalence, Management, and Outcome of Steven Johnson Syndrome and Toxic Epidermal Necrolysis in Pregnant Patients : A Comprehensive Systematic Review - Deanurva Calista Prima; Wahyu Rhomadon (The International Journal of Medical Science and Health Research, 2025)
Background: Toxic epidermal necrolysis (TEN) and Stevens-Johnson syndrome (SJS) are uncommon, potentially fatal cutaneous drug reactions that affect the skin and mucous membranes and are thought to be different manifestations of the same illness. The aim: The purpose of this study is to demonstrate the incidence, treatment, and prognosis of toxic epidermal necrolysis and Steven Johnson syndrome in pregnant individuals. Methods: The Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 was utilized to demonstrate that this study complied with all applicable standards. With this search strategy, articles published between 2014 and 2024 were taken into consideration. This was accomplished by utilizing a number of distinct online reference sites, including Sciencedirect, Pubmed, and SagePub. It was determined that reviews, previously published works, and partially completed works would not be included. Result: Following a thorough three-level screening process, eight publications were determined to be closely connected to our ongoing systematic examination. Following that, an extensive examination of the entire text was carried out, and these articles were subjected to further inspection. Conclusion: SJS/TEN during pregnancy seems to be benign and is linked to good outcomes for both the mother and the fetus, with the exception of a higher risk of preterm birth. The extreme form of the illness, known as TEN, has been linked to worse outcomes for fetuses. Pregnant HIV-positive women do not have an increase in SJS/TEN-associated mortality. It doesn't appear that maternal SJS/TEN frequently shows up in the fetus.